Solute carrier transporter disease and developmental and epileptic encephalopathy - Gan, Yajing; Wei, Zihan; Liu, Chao; Li, Guoyan; Feng, Yan; Deng, Yanchun (Frontiers in Neurology, 2022)
The International League Against Epilepsy officially revised its classification in 2017, which amended “epileptic encephalopathy” to “developmental and epileptic encephalopathy”. With the development of genetic testing technology, an increasing number of genes that cause developmental and epileptic encephalopathies are being identified. Among these, solute transporter dysfunction is part of the etiology of developmental and epileptic encephalopathies. Solute carrier transporters play an essential physiological function in the human body, and their dysfunction is associated with various human diseases. Therefore, in-depth studies of developmental and epileptic encephalopathies caused by solute carrier transporter dysfunction can help develop new therapeutic modalities to facilitate the treatment of refractory epilepsy and improve patient prognosis. In this article, the concept of transporter protein disorders is first proposed, and nine developmental and epileptic encephalopathies caused by solute carrier transporter dysfunction are described in detail in terms of pathogenesis, clinical manifestations, ancillary tests, and precise treatment to provide ideas for the precise treatment of epilepsy.